2013
DOI: 10.1371/journal.pone.0071295
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Three Dose On-Time Compliance with HPV4 Vaccination in a Disadvantaged, Underserved, Safety Net Population in the US Midwest

Abstract: BackgroundHPV4 is approved as a series of three timed doses expected to result in efficacy against specific HPV infections. Completion rates in the US are quite low at the same time the structure of health care delivery is changing. The aim of this study was to determine how the patient-, clinic- and systems-level characteristics facilitate or hinder the timely completion of three HPV4 doses in both adolescent and adult female populations in a high-risk safety net population.MethodsThis is a retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Although there have been millions of doses of HPV4 sold every year [38], [39], our study and others [6], [8][25], show that 66% of the doses are administered in an inefficient manner, making the HPV4 vaccination program unlikely to realize a measurable benefit especially in populations most at-risk, such as our safety net system. Of the inefficiencies, “less than three doses” was more common than inappropriate timing of doses.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Although there have been millions of doses of HPV4 sold every year [38], [39], our study and others [6], [8][25], show that 66% of the doses are administered in an inefficient manner, making the HPV4 vaccination program unlikely to realize a measurable benefit especially in populations most at-risk, such as our safety net system. Of the inefficiencies, “less than three doses” was more common than inappropriate timing of doses.…”
Section: Discussionmentioning
confidence: 78%
“…Only female recipients 10–26 years old were targeted for vaccination. Prior research identified age, race, and parity as positive predictors of on-time three dose completion [6], and hence these person descriptors were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We adjusted results for covariates known to correlate with vaccination coverage: child's and parent's age, race, parent's education level, household income, parent's marital status, parent's primary language, receipt of vaccine in a private or public health facility, insurance status, number of medical visits in the past year, and provider recommendation. [41][42][43] Because HPV vaccination coverage changed over time, we considered each year separately as well as pooling data from all years together. Random effects logistic regression models were used to estimate adjusted HPV vaccination coverage rates adjusting for these covariates, year, and the systematic unobserved variation arising from clustering of observations at the state level.…”
Section: Methodsmentioning
confidence: 99%